2011
DOI: 10.1177/1059840511408322
|View full text |Cite
|
Sign up to set email alerts
|

Health Promotion and Risk Behaviors Among Adolescents in Turkey

Abstract: Adolescents experience the onset and development of several health-related behaviors. The purpose of this study is to determine health risk and promotion behaviors of adolescents between the ages of 11 and 19 who were attending and to test the reliability and validity analysis of the Turkish version of Adolescent Health Promotion Scale (AHPS). The study was a cross-sectional survey and the sample consisted of 1,351 participants. A questionnaire that included demographic information, health risk behaviors, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
46
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 35 publications
10
46
1
7
Order By: Relevance
“…Considering the participants' age and school year, levels of health-promoting behaviors were higher among younger adolescents 5 and those in more advanced grades, namely between age and total behaviors, nutritional behaviors, social support and exercise behaviors, and between school year and nutritional behaviors, exercise behaviors, stress management and total behaviors. Nonetheless, other studies with similar results found that health-promoting nutritional behaviors were more common among older adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the participants' age and school year, levels of health-promoting behaviors were higher among younger adolescents 5 and those in more advanced grades, namely between age and total behaviors, nutritional behaviors, social support and exercise behaviors, and between school year and nutritional behaviors, exercise behaviors, stress management and total behaviors. Nonetheless, other studies with similar results found that health-promoting nutritional behaviors were more common among older adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…3 Levels of health-promoting behaviors were higher in female than male participants, but they were not statistically significant, contrary to other studies that found much more accentuated differences. 3,5 Such differences between genders demonstrate the need for distinct interventions focused on the lowest-scoring health-promoting behaviors for each group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second part consisted of a questionnaire form which investigated the type of internet access of the students, the period of usage of internet, which activities in the internet they participated in and with what frequency they participated in these activities, which was established as a result of literature screening perTurk Pediatri Ars 2016; 51: [22][23][24][25][26][27][28][29][30][31][32][33][34] Çavdar et al Health behaviors in adolescents formed by the investigators and face to face interviews with the young individuals and which took its final shape as a result of a pilot study. In this study, only the time of usage of internet was included in the evaluation among these questions.…”
Section: Data Collection Tools Used In the Studymentioning
confidence: 99%